Prealbumin is a more sensitive marker than albumin to assess the nutritional status in patients undergoing radiotherapy for head and neck cancer - Unal, Dilek; Orhan, Okan; Eroglu, Celalettin; Kaplan, Bunyamin (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : The aim of this prospective study was to determine the prevalence of malnutrition and to evaluate a more sensitive marker to assess the nutritional status in patients undergoing RT for head and neck cancer. Material and methods : The prospective study included 51 (mean age of 57.6 ±11.2 years) patients undergoing RT for head and neck cancer. Malnutrition was defined as weight loss > 5% of baseline. Results: Forty-six (90.2%) of 51 patients were male. Malnutrition developed in 33 (64.7%) patients during RT. Mean prealbumin level was significantly lower in patients with malnutrition than in those without malnutrition (17 ±5 g/dl vs. 22 ±5 g/dl, respectively, p = 0.004). On the other hand, there was no significant difference between the two groups in terms of other nutrition parameters including total protein, albumin, total cholesterol, triglyceride, and glucose (p > 0.05). The percentage of weight loss negatively correlated with prealbumin (r = –0.430, p = 0.002), but not with other nutrition parameters including total protein, albumin, triglyceride, total cholesterol, HDL cholesterol, LDL cholesterol, and glucose (p > 0.05). Conclusions : The prevalence of malnutrition was high in patients with head and neck cancer. Prealbumin was a more sensitive marker than albumin to assess the nutritional status in these patients.